Descriptive Study of Rsv Infection in Preterm Infants - López Escobar, Alejandro; Benedit Gómez, M.; Fernández Díaz, M.; Llana Martín, I.; Jimeno Ruiz, Sara (My University, 2024)
Objectives: Description of RSV infection in preterm infants below two months of age. Methods: Descriptive and retrospective study of infants less than two months old admitted to hospital with the diagnosis of RSV infection from January-2004 to December-2010. Comparison between preterm and non-preterm patients. Results: 250 children below two months of age were admitted to hospital during the period of study with diagnosis of RSV infection. 38 of them were preterm (33.92+/-1.98w). The mean age at time of diagnosis was 32.69+/- 15.3d of age. 10 % of the preterm infants presented apnoea and 89,5% developed bronchiolitis. 42% of the preterm patients required PICU admission which is a higher percentage compared to non term infants (p 0,045). Compared to non preterm patients, preterm infants admitted to UCIP presented apnoea more frecuently (31%) and needed more often respiratory assistance, either with CPAP (68,7%) or with mechanical ventilation support (31%). However, these differences were not significant (p0,08). While in the paediatric floor, preterm patients needed suplementary oxigen more frecuently and for longer periods than term infants. No significant differences were found regarding the rest of the variables analysed. Discussion: Preterm infants less than two months old with RSV infection suffer from a higher risk of admission to PICU and need treatment more frecuently than non-preterm patients.